Acute Coronary Syndrome in Patients with Epilepsy: A Narrative Review - Dwi Putra Haliim (Jurnal Ilmu Kedokteran dan Kesehatan, 2026)
Acute coronary syndrome (ACS) is a major public health burden with particularly high prevalence among people with epilepsy, which complicates risk stratification, management, and outcomes. This review followed the PRISMA guideline and literature search was performed on PubMed, Scopus, and Science Direct. Inclusion criteria included original research with cohort, case-control, or cross-sectional design comparing ACS prevalence in populations with and without epilepsy. A total of 936 studies were retrieved and seven studies were included in this review. All included studies had low risk of bias. Qualitative analysis of extracted data reveals that epilepsy independently increases the risk of ACS, particularly acute myocardial infarction, and is consistently associated with poorer prognosis relative to the general population. Notably, the analysis unraveled two clusters of risk factors: conventional cardiovascular risks (e.g., older age, metabolic comorbidities, atherosclerosis) and epilepsy-specific factors (e.g., epilepsy-related hospitalizations, specific antiepileptic drug regimens). The latter suggests that disease management choices may exacerbate cardiovascular vulnerability. These findings imply that current cardiovascular risk models are insufficient for epilepsy patients, and they underscore a critical need for multidisciplinary strategies that directly address epilepsy-specific challenges to improve clinical outcomes.